Performance Comparison of Dispersion Compensation Schemes Using DCF in DWDM Optical Network - Fauza Khair; Dodi Zulherman; Fahmi Fahmi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
The dense wavelength division multiplexing (DWDM) system enhances bandwidth capacity for long-haul communications system, but the system performance is affected by a chromatic dispersion especially in the high bitrate communication caused by different refractive index in pulse propagation for optical link. Using the Dispersion compensating fiber (DCF) can compensate for the positive dispersion in the optical link because it has negative dispersion value and can reduce the effect of the chromatic dispersion. We look for the suitable DCF scheme in our DWDM System using 16 channels with bitrate 40 Gbps per channel, channel spacing 200 GHz and optical link length 300 km and discuss the system performance to compensate dispersion in DWDM systems with the optical launch power variation. Based on the result, the system with the symmetrical scheme with optical power launch had the best performance with BER 8.33 × 10-86 and Q-factor 19.572. Optical power launch had the effect to the system performance, the optical power launch 0 dBm in the all DCF scheme was not meet with ITU-T standard for optical link. In sequentially Q-factor of the pre-compensating, post compensating, and symmetrical compensating fiber schemes is 6.007, 6.209, and 6.608 which are not meet the ITU-T standard that Q-factor has to more than 7.20. The increasing optical power launch improved the system performance for all DCF scheme. In sequentially Q-factor of the symmetrical scheme with input power 0 dBm, 2 dBm, 4 dBm, 6 dBm, 8 dBm, and 10 dBm is 6.680, 8.510, 10.724. 13.340, 16.319, 19.572. This work obtains that the system with symmetrical compensating fiber more suitable than pre-compensating fiber and post-compensating fiber and the system with high optical launch power has better performance than low power.